1992
DOI: 10.1034/j.1600-0889.1992.t01-4-00002.x
|View full text |Cite
|
Sign up to set email alerts
|

The Po Valley Fog Experiment 1989.

Abstract: An outline is presented here of the Po Valley Fog Experiment 1989, carried out within the EUROTRAC‐GCE project. This experiment is a joint effort by several European research groups from 5 countries. The physical and chemical behaviour of the fog multiphase system was studied experimentally following the temporal evolution of the relevant chemical species in the different phases (gas, droplet, interstitial aerosol) and the evolution of micrometeorological and microphysical conditions, from the pre‐fog situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 39 publications
2
36
0
2
Order By: Relevance
“…Our focus is in the development of the size distributions and droplet chemical compositions as a function of time, and in the reduction of visibility. Although the ammonia mixing ratios used in this study are comparable to those found for example in the Po Valley area (Fuzzi et al, 1992), and high nitrate concentrations have been found in fogwater in California (Jacob et al, 1985), we are not trying to specifically model any observed pollution fogs, but rather to take a step forward from the simple Köhler theory calculations, in order to qualitatively find out which kind of effects soluble trace gases may have on fog formation at heavily polluted conditions. Our future goal is to model observed pollution fogs; however, that will require more sophisticated models than those used in the present study.…”
Section: Introductionmentioning
confidence: 89%
“…Our focus is in the development of the size distributions and droplet chemical compositions as a function of time, and in the reduction of visibility. Although the ammonia mixing ratios used in this study are comparable to those found for example in the Po Valley area (Fuzzi et al, 1992), and high nitrate concentrations have been found in fogwater in California (Jacob et al, 1985), we are not trying to specifically model any observed pollution fogs, but rather to take a step forward from the simple Köhler theory calculations, in order to qualitatively find out which kind of effects soluble trace gases may have on fog formation at heavily polluted conditions. Our future goal is to model observed pollution fogs; however, that will require more sophisticated models than those used in the present study.…”
Section: Introductionmentioning
confidence: 89%
“…In order to better understand this structure, measurements during various field experiments have been obtained over the last 200 years (i.e. Wells, 1814;Willett, 1928;Fuzzi et al, 1998;Tardif and Rasmussen, 2007). PARISFOG and TOULOUSEFOG are the most recent field experiments.…”
Section: Introductionmentioning
confidence: 99%
“…[3] In this letter, aerosol properties derived from optical measurements are described for the Po Valley, a heavily populated region in northern Italy, with high agricultural and industrial activity, and elevated levels of aerosols, haze and fog [Fuzzi et al, 1998]. The measurements are based on 7-year time series provided by two sun-photometers located at the two ends of the valley.…”
Section: Introductionmentioning
confidence: 99%